First record of the thermosbaenacean genus Halosbaena from Asia: H. daitoensis sp. nov. (Peracarida: Thermosbaenacea: Halosbaenidae) from an anchialine cave of Minamidaito-jima Is., in Okinawa, southern Japan - Shimomura, Michitaka; Fujita, Yoshihisa (Zootaxa, 2009)
A new species of Halosbaena is described from Japan as the first record of the genus from Asia. Halosbaena daitoensis sp. nov. differs from its congeners in the following combination of characters: rounded mediodistal angle of ocular scales; 12–14 segmented main flagellum of antenna 1; segment 2 of exopodite of pereiopods 2–5 with 8 plumose macrosetae; segment 2 of uropodal exopodite with 9 plumose macrosetae; telson about 0.6 times as width as length; distally tapering male penial lobe, with a short projection on its base. A key to species of the genus is provided.